Comprehensive Investigation of Stereoselective Food Drug Interaction Potential of Resveratrol on Nine P450 and Six UGT Isoforms in Human Liver Microsomes - Seung-Bae Ji; So-Young Park; Subin Bae; Hyung-Ju Seo; Sin-Eun Kim; Gyung-Min Lee; Zhexue Wu; Kwang-Hyeon Liu (MDPI AG, 2021)
The stereoselectivity of the food drug inhibition potential of resveratrol on cytochrome P450s and uridine 5'-diphosphoglucuronosyl transferases was investigated in human liver microsomes. Resveratrol enantiomers showed stereoselective inhibition of CYP2C9, CYP3A, and UGT1A1. The inhibitions of CYP1A2, CYP2B6, and CYP2C19 by resveratrol were stereo-nonselective. The estimated Ki values determined for CYP1A2 were 13.8 and 9.2 μM for trans- and cis-resveratrol, respectively. Trans-resveratrol noncompetitively inhibited CYP3A and UGT1A1 activities with Ki values of 23.8 and 27.4 μM, respectively. Trans-resveratrol inhibited CYP1A2, CYP2C19, CYP2E1, and CYP3A in a time-dependent manner with Ki shift values >2.0, while cis-resveratrol time-dependently inhibited CYP2C19 and CYP2E1. The time-dependent inhibition of trans-resveratrol against CYP3A4, CYP2E1, CYP2C19, and CYP1A2 was elucidated using glutathione as a trapping reagent. This information helped the prediction of food drug interaction potentials between resveratrol and co-administered drugs which are mainly metabolized by UGT1A1, CYP1A2, CYP2C19, CYP2E1, and CYP3A.